Income variation, endogenous population growth and health subsidy - Gómez, Manuel; Currais, Luis (Estudios de Economía, 2016)
This paper presents a fertility choice model in which the mortality rate is also endogenously determined and health expenditure provides utility to individuals as well as affects the mortality rate. The analysis shows that the model predictions agree with the empirical evidence on the relationship between demography trends and economic development. Public expenditure represents a large amount of total expenditure on health care in many countries. Thus, we also study the effects that introducing a subsidy to health expenditure has on economic and demographic variables. These effects are found to depend on the way the subsidy is financed.